The Potential of Herbal Combinations as Adjunctive Therapy for Standard Care of COVID-19 Patients: A Lesson Learned from Indonesia - Rozaliyani, Anna; Pratama, Satria; Setianingrum, Findra; Yunita, Fenny; Rumende, C. Martin (UI Scholars Hub, 2023)
The pandemic of novel coronavirus disease (COVID-19) has become a global disaster that occurred between the end of 2019 and 2023. It caused immeasurable damage to almost all aspects of human life. The disease has opened a lot of new perspectives on Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) origins and pathogenesis, the nature of the virus, the potential for new treatments, and new policies to overcome this pandemic. This review aims to know the potential of plants that are beneficial to combat the diseases, including immunomodulators in the management of COVID-19. Studies reporting COVID-19 with the keywords SARS-CoV-2, COVID-19, pathogenesis, clinical manifestations, medicinal plants, and their benefits were included. We also discussed the molecular pathways of the bioactive compound that may interact with the pathogenesis of COVID-19. Clinical management for COVID-19 is still being refined from time to time because many aspects are not yet fully understood and need further studies. Therefore, effective, non-invasive, and affordable treatment must be sought immediately to meet this very urgent need. The commotion situation of the COVID-19 pandemic has encouraged various efforts to develop new drugs, including alternative therapies from potential medicinal plants. The pharmacotherapeutic activity of Indonesia-based medicinal plants for COVID-19 has evolved, including Phyllanthus niruri, Andrographis paniculata, Anacardium occidentale, Zingiber officinale, and Glycyrrhiza glabra. The potential benefits of that combination of herbal medicinal plants also need to be explored for better contribution in managing COVID-19, particularly in Indonesia.